Diagnostic accuracy and cut-off of contrast-enhanced ultrasound in caesarean scar pregnancy. (March 2020) - Li, Haiying; Liu, Xinxiu; Xie, Lijun; Ye, Zhen; Gan, Ling
Abstract: Objectives: To investigate the diagnostic accuracy of contrast-enhanced ultrasound (CEUS) and to search for cut-offs in caesarean scar pregnancy (CSP) patients for making quantitative diagnoses. Study Design: Thirty patients in the first trimester of pregnancy were enrolled in our study. They were suspected as being at risk of caesarean scar pregnancy by conventional ultrasound and insisted on abortions. Transvaginal ultrasonography (TVU) and CEUS were performed, and parameters were analysed on the time-intensity curve (TIC). Laparotomy, laparoscopy, hysteroscopy or curettage under the guidance of ultrasound were performed, and pathological finding of villi in the uterine scar is the gold standard for a diagnosis of CSP. The area under the receiver operating characteristic (ROC) curve (AUC) was used to estimate the probability of the correct prediction of CSP. Results: CSP was diagnosed in 27 patients: pathological diagnosis revealed villus tissue in the scar. The peak intensity ratios of caesarean scar to myometrium have the overall best diagnostic performances (AUC: 0.877, 95 % CI: 0.74–1.00). Using a cut-off value of 1.08 for the peak intensity ratio of caesarean scar to myometrium, the diagnosis sensitivity, specificity, PPV and NPV for CSP were 77.8, 100, 100, and 81.8 %, respectively. Conclusions: CEUS offers good diagnostic performance, and the peak intensity ratio of caesarean scar to myometrium can be used as a quantitative index to diagnose CSP accurately.